Early neonatal Chlamydia trachomatis pneumonia: A case report - K, Sunkonkit; S, Reungrongrat (Biomedical Sciences and Clinical Medicine, 2019)
Chlamydia trachomatis pneumonia, a cause of pneumonia in infancy, results from perinatal transmission from an infected mother to a newborn. Early diagnosis and intervention are necessary to prevent hypoxia and other complications. Our study is the firs case report that describes the presentation of an 11-day-old female infant diagnosed at the early onset of Chlamydia trachomatis pneumonia. We report the clinical presentation and clinical course of the child with Chlamydia trachomatis pneumonia at Chiang Mai University Hospital. For young infants who present with tachypnea and a persistent cough, where hyperinflation is evident on a chest X-ray, and where symptoms do not improve with conventional treatment, Chlamydia trachomatis infection may be the cause of the infection.